Специфіка художнього психологізму в творчості письменннків-родичів крізь призму спадкових психічних властивостей - Стасюк, Г. (Літературознавчі обрії. Праці молодих учених, 2010)
The article deals with the problem of correlation of hereditary psychical traits of writers-relatives and basic peculiarities of dynastic artistic psychologism. The basis of Kosach-Dragomanov gifted family is analyzed. The nature of influence of hereditary disposition on artistic direction of image creation is traced.